Selective Migration of Subpopulations of Bone Marrow Cells along an SDF-1α and ATP Gradient. (31st December 2014) - Laupheimer, Michael; Skorska, Anna; Große, Jana; Tiedemann, Gudrun; Steinhoff, Gustav; David, Robert; Lux, Cornelia A.
Abstract : Both stem cell chemokine stromal cell-derived factor-1 α (SDF-1 α ) and extracellular nucleotides such as adenosine triphosphate (ATP) are increased in ischemic myocardium. Since ATP has been reported to influence cell migration, we analysed the migratory response of bone marrow cells towards a combination of SDF-1 and ATP. Total nucleated cells (BM-TNCs) were isolated from bone marrow of cardiac surgery patients. Migration assays were performed in vitro . Subsequently, migrated cells were subjected to multicolor flow cytometric analysis of CD133, CD34, CD117, CD184, CD309, and CD14 expression. BM-TNCs migrated significantly towards a combination of SDF-1 and ATP. The proportions of CD34+ cells as well as subpopulations coexpressing multiple stem cell markers were selectively enhanced after migration towards SDF-1 or SDF-1 + ATP. After spontaneous migration, significantly fewer stem cells and CD184+ cells were detected. Direct incubation with SDF-1 led to a reduction of CD184+ but not stem cell marker-positive cells, while incubation with ATP significantly increased CD14+ percentage. In summary, we found that while a combination of SDF-1 and ATP elicited strong migration of BM-TNCs in vitro, only SDF-1 was responsible for selective attraction of hematopoietic stem cells. Meanwhile, spontaneous migration of stem cells was lower compared to BM-TNCs or monocytes.